2006
DOI: 10.1172/jci29812
|View full text |Cite
|
Sign up to set email alerts
|

Deiodinases: implications of the local control of thyroid hormone action

Abstract: The deiodinases activate or inactivate thyroid hormone, and their importance in thyroid hormone homeostasis has become increasingly clear with the availability of deiodinase-deficient animals. At the same time, heightened interest in the field has been generated following the discovery that the type 2 deiodinase can be an important component in both the Hedgehog signaling pathway and the G protein-coupled bile acid receptor 1-mediated (GPBAR1-mediated) signaling cascade. The discovery of these new roles for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
552
1
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 726 publications
(582 citation statements)
references
References 107 publications
12
552
1
17
Order By: Relevance
“…Compound 2 increased TG mRNA as effectively as TSH and increased mRNAs for TPO, NIS, and DIO2 somewhat less effectively than TSH. We also measured the effects of compound 2 on DIO2 by assaying its enzymatic activity to de-iodinate T4 to tri-iodothyronine (28). Both TSH and compound 2 increased DIO2 protein activity (Fig.…”
Section: Compound 2 Stimulates Thyroid-specific Gene Expression In Prmentioning
confidence: 99%
“…Compound 2 increased TG mRNA as effectively as TSH and increased mRNAs for TPO, NIS, and DIO2 somewhat less effectively than TSH. We also measured the effects of compound 2 on DIO2 by assaying its enzymatic activity to de-iodinate T4 to tri-iodothyronine (28). Both TSH and compound 2 increased DIO2 protein activity (Fig.…”
Section: Compound 2 Stimulates Thyroid-specific Gene Expression In Prmentioning
confidence: 99%
“…Type 2 deiodinase (D2) activates the prohormone thyroxine (T4) by converting it to thyroid hormone (T3), whereas D3, by inactivating T3, terminates thyroid hormone action (1). All vertebrates express D2 and D3 that, in adults, contribute to plasma T3 and T4 homeostasis by their concerted actions with the hypothalamic-pituitary feedback axis.…”
mentioning
confidence: 99%
“…Recently, it has been shown that this reduction is regulated by biotinization of D2 [28]. D2 ubiquitination accelerates in proportion to T4 concentration, creating a feedback loop controlling D2-mediated T3 production [28,29].…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%